2011
DOI: 10.1111/j.1745-8315.2011.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalysis and the United States research university: Current trends

Abstract: In this essay the author describes the status of the humanities within United States research universities, and notes that there is a place in the research university for clinical analysts with non-quantitative research interests, who are seen as humanities scholars by other humanities specialists. He discusses the current trend in psychoanalytic research in the United States, which perpetuates an historically well-known divide between quantitative and non-quantitative investigators, and causes non-quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A good approach would be to combine epistemological aspects with considerations of ‘good psychotherapy’ in university teaching (e.g. to draw attention to such problems as the bias towards quantitative empirical teaching, especially in psychology, and eclecticism – see Epstein, ; Sonnenberg, ). Attempts should also be made to demonstrate the practicability of psychoanalysis too with patients, for instance by means of student seminars on the conduct of interviews.…”
Section: Interpretative Résumé Of the Principal Results And Conclusionmentioning
confidence: 99%
“…A good approach would be to combine epistemological aspects with considerations of ‘good psychotherapy’ in university teaching (e.g. to draw attention to such problems as the bias towards quantitative empirical teaching, especially in psychology, and eclecticism – see Epstein, ; Sonnenberg, ). Attempts should also be made to demonstrate the practicability of psychoanalysis too with patients, for instance by means of student seminars on the conduct of interviews.…”
Section: Interpretative Résumé Of the Principal Results And Conclusionmentioning
confidence: 99%
“…There has been far less attention paid to the converse issue of how the university may (or may not) desire psychoanalysis. Freud's formulation is that psychoanalysis can contribute to the university, but there has been less recognition of how the university can contribute to psychoanalysis (Sonnenberg, ) and not just in the sense of how the university may help psychoanalysis solve its problems without altering its fundamentals. Psychoanalysis and formal academia are set up in opposition and the debate is in danger of being one‐sided.…”
Section: The Programme In Contextmentioning
confidence: 99%
“…For example, it has been observed that “academic life is regulated by laws and rules that are logically incongruous with psychoanalysis” (Filho and Horizonte, , p. 91), that university discourse has no room for subjectivity (Ferrari, ) and that scientific research is incompatible with psychoanalytic research (Hoffman, ; Stern, ). In contrast, Sonnenberg () describes a mutually productive partnership in a humanities faculty in the United States, and Paul () points out that “universities are likely to have more very smart people per square yard knowledgeable about and interested in psychoanalysis than any other sort of community” (p. 995). The reality is that psychoanalysis as a theory, and even as a practice (albeit often in modified forms), has been a vibrant part of various university disciplines for decades.…”
Section: The Programme In Contextmentioning
confidence: 99%
See 2 more Smart Citations